Penggunaan Teknik Mixing Foundation untuk Menghasilkan Warna Natural pada Tone Kulit Wajah Gelap untuk Make Up Foto Beauty - Maulina, Dianisa; Lutfiati, Dewi (Universitas Negeri Surabaya, 2021)
Foundation mixing technique is a technique of mixing more than one foundation that is used in order to create the desired color. The problem faced by make-up artists for clients with dark facial skin is that the foundation does not match the skin color due to the limited color of the foundation. This can create new innovations in makeup to produce natural colors on dark facial skin. The purpose of this study to find out: 1) the suitability of the results of the mixing foundation technique on dark facial skin tones. 2) The observer's favorite of mixing foundations for dark facial skin tones on beauty photo opportunities. This type of research is experimental. The variables in this study consisted of independent variables: mixing foundations with dark colors and natural colors with a ratio of X1 (3gr: 3gr), X2 (4.5gr: 1.5gr), X3 (5gr: 1gr). The dependent variable is the result of beauty photo make up which includes: foundation color with the most suitable mixing technique for dark facial skin, application of suitable foundation mix on facial skin, beauty photo results. The data collection method used google form and involved 35 observers. The data analysis technique used the one way Anava test followed by the Duncan test using the SPSS version program 21. The research results showed that 1) a mixing foundation that is suitable for dark facial skin tones is in the ratio X2 which has the highest average value 2) the results of mixing foundation For dark face skin tones on the occasion of beauty photos according to the observer the most preferred and in accordance with the assessment criteria is in the photo with a comparison of X2 with the highest average value of 3.66 Keyword: mixing foundation, dark face skin, photo make-up